Forecast of athletic achievements based on artificial neural networks - Wang, Z.; Lu, G.; Xu, G. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
Introduction Artificial Neural Network-ANN is a network information system which is build on the basis of brain feedback information, this system has high nonlinear disposal ability. The article adopts the BP method of artificial neural network to forecast athletic achievements. Methods BP method of artificial neural network, mathematical method Results 1. Forecast of Athletic Achievements To illustrate this method, we build a model by the means of numerical value test. We take the national backstroke record from1991 to 1997 as learning stylebooks, to forecast later year`s achievement. In this model, we forecast the achievement of later l year (l=1) according to the achievement of former m year (m=3).